Medium effects in proton-induced $K^{0}$ production at 3.5 GeV - HADES collaboration (97 authors) (2014)
We present the analysis of the inclusive K0 production in p+p and p+Nb collisions measured with the HADES detector (GSI Helmholtzzentrum for Heavy-Ion Research, Darmstadt) at a beam kinetic energy of 3.5 GeV. Data are compared to the Giessen Boltzmann-Uehling-Uhlenbeck (GiBUU) transport model. The data suggest the presence of a repulsive momentum-dependent kaon potential as predicted by the chiral perturbation theory (ChPT). For the kaon at rest and at normal nuclear density, the ChPT potential amounts to ≈35 MeV. A detailed tuning of the kaon production cross sections implemented in the model has been carried out to reproduce the experimental data measured in p+p collisions. The uncertainties in the parameters of the model were examined with respect to the sensitivity of the experimental results from p+Nb collisions to the in-medium kaon potential.